An Act Defining Crime and Punishments, 121, Ch. 49, Sec. 21-22, in Revised Statutes of the Territory of Iowa (Reprint 1911) - (:unkn) unknown (My University, 1843)
Prohibited challenging another or accepting an offer to duel, or participating as a second or promoter. Violators fined not less than five hundred dollars, nor more than two thousand dollars. Violators where death ensues shall be guilty of murder.
Keywords: DUELING